2021
DOI: 10.1007/s11084-021-09615-2
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the Stability of Natural Amino Acid isomers

Abstract: The secular debate on the origin of life on our planet represents one of the open challenges for the scientific community. In this endeavour, chemistry has a pivotal role in disclosing novel scenarios that allow us to understand how the formation of simple organic molecules would be possible in the early primitive geological ages of Earth. Amino acids play a crucial role in biological processes. They are known to be formed in experiments simulating primitive conditions and were found in meteoric samples retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Even if there are some theoretical works showing that the actual enantiomers present in biomolecules are the most stable, like D-glyceraldehyde in gas-phase (Kikuchi et al 2002) and in solution (Kitayama et al 2002a, b) for amino acids it is less evident (Laerdahl et al 2000;Bergerd and Quack 2000;MacDermott et al 2009;Lee et al 2004;Kitayama et al 2002a, b) a complete cause-effect is not clear (Avalos et al 2000). Our own research group demonstrated, the existence of natural amino acids isomers showing thermodynamical stability higher compared to the rest by investigation over 100′000 structural isomers of natural amino acids (Crespi et al 2021).…”
Section: Introductionmentioning
confidence: 95%
“…Even if there are some theoretical works showing that the actual enantiomers present in biomolecules are the most stable, like D-glyceraldehyde in gas-phase (Kikuchi et al 2002) and in solution (Kitayama et al 2002a, b) for amino acids it is less evident (Laerdahl et al 2000;Bergerd and Quack 2000;MacDermott et al 2009;Lee et al 2004;Kitayama et al 2002a, b) a complete cause-effect is not clear (Avalos et al 2000). Our own research group demonstrated, the existence of natural amino acids isomers showing thermodynamical stability higher compared to the rest by investigation over 100′000 structural isomers of natural amino acids (Crespi et al 2021).…”
Section: Introductionmentioning
confidence: 95%
“…Even if there are some theoretical works showing that the actual enantiomers present in biomolecules are the most stable, like D-glyceraldehyde in gas-phase (Kikuchi et al 2002) and in solution (Kitayama et al 2002) for amino acids it is less evident (Laerdahl 2000 (Avalos et al 2000). Our own research group demonstrated that natural alpha amino acids showing higher thermodynamical stability compared to their structural isomers of the rest by investigation on over 100′000 isomers (Crespi et al 2021).…”
Section: Introductionmentioning
confidence: 99%